Disseminated Scedosporium apiospermum infection with leprosy responsive to voriconazole. Issue 3 (September 2014) - Verma, Santwana; Minhas, Samridhi; Verma, G. K.; Shanker, Vinay; Tegta, G. R.; Sharma, Surdarshan; Kanga, Anil; Asotra, Sanjeev; Gautam, Neha
Abstract : Introduction: Scedosporium apiospermum is a significant emerging fungus causing potentially life‐threatening infections in poor immune responders. Scedosporiosis may complicate chronic diseases such as leprosy rarely presenting with fungaemia and extensive cutaneous lesions resistant to treatment. Case presentation: An elderly female presented with numerous red, painful, pustules over distal extremities spanning 2 months. Fever and numbness of hands and feet were associated features. A past history of a fall 3 years previously traumatizing the lower back followed by joint pains and self‐medication with steroids were antecedent factors as well as uncontrolled diabetes. She was a case of lepromatous leprosy released from multidrug therapy, the period ahead of which was interspersed with episodes of erythema nodosum leprosum. Examination revealed multiple erythematous nodulo‐plaques, pus‐filled bullae and hyperpigmented verrucous plaques over limbs with black skin discoloration and puckered scars over the right thigh and buttocks. Imaging showed sclerosis of pelvic bones and wedge compression of the lumbosacral spine. Direct microscopy of pus demonstrated branched, septate, hyaline hyphae and closely septate swollen cells in periodic acid–Schiff‐stained tissue sections. S. apiospermum isolated in cultures of pus and blood depicted fungaemia and this was further substantiated by echocardiographic visualization of echogenic nodules on the anterior mitral leaflet. A transient favourable response on itraconazole 200–400 mg daily was followed by the emergence of new lesions. Parenteral voriconazole at 4–6 mg kg −1 followed by oral treatment at 400 mg daily showed satisfactory improvement. The final outcome remained obscure as the patient was lost to follow‐up. Conclusion: Therapy‐resistant cutaneous lesions in chronic diseases such as leprosy should be evaluated for rare opportunistic fungal infections.